2014
DOI: 10.1186/s12967-014-0274-2
|View full text |Cite
|
Sign up to set email alerts
|

Human urine-derived stem cells in combination with polycaprolactone/gelatin nanofibrous membranes enhance wound healing by promoting angiogenesis

Abstract: BackgroundDespite advancements in wound healing techniques and devices, new treatments are needed to improve therapeutic outcomes. This study aimed to evaluate the potential use of a new biomaterial engineered from human urine-derived stem cells (USCs) and polycaprolactone/gelatin (PCL/GT) for wound healing.MethodsUSCs were isolated from healthy individuals. To fabricate PCL/GT composite meshes, twin-nozzle electrospinning were used to spin the PCL and gelatin solutions in normal organic solvents. The morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 45 publications
6
64
1
Order By: Relevance
“…Meanwhile, the expression of type X collagen is the typical features of chondrocyte hypertrophy 20-24. These observed indicators were commensurate with previously reported results, and were adopted to measure the chondrogenesis process 25-29.…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, the expression of type X collagen is the typical features of chondrocyte hypertrophy 20-24. These observed indicators were commensurate with previously reported results, and were adopted to measure the chondrogenesis process 25-29.…”
Section: Discussionsupporting
confidence: 84%
“…In previous urological studies, USCs were used to construct tissue-engineered conduits for urinary diversion [15] and to ameliorate erectile dysfunction [16,17]. Moreover, we found that USCs combined with bioactive materials accelerated skin-wound healing in rabbits [18] and that USCs can survive in and migrate to other parenchymal areas and differentiate into neuron-like cells in the rat brain [13].…”
Section: Introductionmentioning
confidence: 88%
“…USCs were isolated from the urine of healthy adult donors, according to the methods described in our previous studies [13,18]. The Ethics Committee of Shanghai Sixth People's Hospital Affiliated with Shanghai Jiaotong University approved the study, and written informed consent was obtained from all the volunteers upon their enrollment in the study.…”
Section: Isolation and Purification Of Uscs-evsmentioning
confidence: 99%
“…[1][2][3] Coaxial electrospinning, comparing to simple single and blended spinning, is used to prepare core-sheath structured nanofibers with outstanding properties and multifunctionality for additional functional applications, [4][5] such as biotechnology, textiles, membranes, composites. [6][7][8][9] Stimuli-responsive polymers have been widely used in intelligent or smart materials with a great promise in drug delivery systems, sensors, and biomaterials, [10][11][12][13][14][15] due to these polymers can respond to changes in temperature, pH, light, or ionic strength. For example, poly(N-isopropylacrylamide) (PNIPAAm) is a typical temperature-sensitive polymer.…”
Section: Introductionmentioning
confidence: 99%